Analytical modeling of chip formation mechanism in cutting unidirectional carbon fiber reinforced polymer. (15th June 2022) - Song, Chunlei; Jin, Xiaoliang
Abstract: Fiber orientation of the unidirectional carbon fiber reinforced polymer (UD CFRP) dominates the chip formation in the cutting process owing to its anisotropy. Existing analytical cutting models focus on cutting force prediction based on the pre-defined chip formation modes obtained from experimental analyses at different fiber orientation ranges. This paper presents the analytical prediction of CFRP chip formation modes, including fiber tension, fiber compression, matrix tension, and matrix compression, based on the stress state in the chip formation region in the fiber orientation range of [ 0 °, 180 ° ] . The chip formation angle and the stresses activating the material failure on the chip formation plane are predicted with the minimum cutting energy principle. The transition of the chip formation mode as the fiber orientation increases, and the variations of the chip morphology and cutting forces owing to the change of chip formation mode are predicted and analyzed. The chip formation angle, chip morphology, and cutting forces are compared between the simulations and the measurements through orthogonal cutting experiments of UD CFRP at different uncut chip thicknesses and fiber orientations.